The Ability of Early Detection of Mental Health in Adolescents with the Provision of Health Education Using Audio Visual Methods at SMK Pawyatan Daha 1 Kediri - Suhita, Byba Melda; Riska Widyastuti (Universitas STRADA Indonesia, 2023)
Background: Adolescent mental health is important in determining the quality of the nation. Early detection of mental health in adolescents is very necessary to provide knowledge and understanding and attention, to avoid and overcome the occurrence of disorders in the subsequent adolescent growth and development. Purpose: The purpose of this study is to determine the ability of early detection of mental health in adolescents with the provision of health education using audio visual. Methods: The design of this study is pre-experimental quantitative research with a one-group pre-post test design approach with the focus of the research directed at analyzing the effect of providing health education using audio-visual methods on the ability to early detection of mental health in adolescents at SMK Pawyatan Daha 1 Kediri. The total population was 394 respondents and a sample of 199 respondents were taken using the Stratifiet Random Sampling technique. Results: The findings found that before being given treatment, most respondents were less able to carry out early detection of mental health as many as 171 respondents (85.93%). After being given treatment, most respondents were able to carry out early detection of mental health as many as 158 respondents (79.40%). Based on the results of Wilcoxon's analysis, it was shown that the p-value of 0.000 < 0.05, then H0 was rejected and H1 was accepted so it was concluded that there was an influence of providing health education using audio-visual methods on the ability to early detection of mental health in adolescents at SMK Pawyatan Daha 1 Kediri. Conclusion: It is hoped that adolescents, especially students at SMK Pawyatan Daha 1 Kediri, can carry out early detection of mental health both to themselves and to others, which can reduce the risk of increased mental disorders or pressures experienced by adolescents.